2011
DOI: 10.1210/jc.2010-2959
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Hormone Levels and Anthropometry in Postmenopausal Women with Polycystic Ovary Syndrome (PCOS): A 21-Year Follow-Up Study of Women Diagnosed with PCOS around 50 Years Ago and Their Age-Matched Controls

Abstract: PCOS women differ from controls with regard to levels of certain reproductive hormones also after menopause, but the established premenopausal increase in waist to hip ratio in PCOS patients disappeared after menopause, mainly due to weight gain among controls. A novel finding was the lower prevalence of hypothyroidism in PCOS women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
113
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(123 citation statements)
references
References 31 publications
9
113
0
1
Order By: Relevance
“…In PCOS, after a steady decrease with age until menopause, the FAI and cFT seemed to increase after the age of 50 years, although with great individual variation. This is in line with the results of previous studies in which it has been suggested that hyperandrogenemia persists or even worsens after menopause in women with PCOS (20,(35)(36)(37). We speculate that the elevation and individual variation of the androgen parameters are probably linked to the significant decrease in SHBG levels, which in turn is linked to increased weight, impaired glucose metabolism, and insulin sensitivity in some of the subjects, as shown in previous studies (19,23,38,39).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In PCOS, after a steady decrease with age until menopause, the FAI and cFT seemed to increase after the age of 50 years, although with great individual variation. This is in line with the results of previous studies in which it has been suggested that hyperandrogenemia persists or even worsens after menopause in women with PCOS (20,(35)(36)(37). We speculate that the elevation and individual variation of the androgen parameters are probably linked to the significant decrease in SHBG levels, which in turn is linked to increased weight, impaired glucose metabolism, and insulin sensitivity in some of the subjects, as shown in previous studies (19,23,38,39).…”
Section: Discussionsupporting
confidence: 93%
“…The strengths of our study are as follows: 1) it covered a large study population including women with PCOS from young fertile age to menopause, the age window being wider than in earlier studies (20,30,33,37); 2) the study population was homogeneous because all women were Caucasians; and 3) we used the gold standard of analysis, liquid chromatography-mass spectrometry, for the assay of T in all subjects. The PCOS cohorts were recruited from five different study sites, but at all sites the Rotterdam criteria for PCOS was used.…”
Section: Discussionmentioning
confidence: 99%
“…This is aggravated if a woman has diabetes and dyslipidemia [20]. On the other hand, another study indicates that these patients had fewer climacteric symptoms than controls [21], further have insulin resistance attenuated. But, there were reports that did not find differences between postmenopausal patients with or without pre-polycystic ovary syndrome [22].…”
Section: Metabolic Disorders During Menopausementioning
confidence: 99%
“…In women with PCOS, symptoms usually start in adolescence and gradually progress during reproductive years (24), with their severity depending on the presence of IR and obesity that is also associated with an increased risk for metabolic abnormalities (25). Although in perimenopause there is an amelioration of the clinical and laboratory features of PCOS (26,27), elevated androgen levels of both ovarian and adrenal origin continue to persist during early postmenopause (14) and remain elevated up to late menopause without exceeding premenopausal levels (28). Although other androgens such as androstanediol glucuronide may also be implicated particularly in the development of hirsutism, there is no data on their potential effect in postmenopausal women with PCOS (29).…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%